2010
DOI: 10.1038/nrclinonc.2010.42
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in VHL as potential biomarkers in renal-cell carcinoma

Abstract: Germ line mutations in the VHL tumor-suppressor gene cause von Hippel-Lindau (VHL) disease, a hereditary neoplastic disease associated with clear-cell renal-cell carcinomas (ccRCCs), central nervous system hemangioblastomas and pheochromocytomas. Disruption of VHL, by somatic mutation, hypermethylation of its promoter or chromosomal loss, is also seen in the majority of cases of sporadic ccRCC. The protein product of VHL, pVHL, has multiple functions, the best-documented of which relates to its ability to targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
116
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 75 publications
7
116
0
2
Order By: Relevance
“…We used a whole genome amplification step, because the yield of DNA extracted from the tumor cells in the cyst walls was frequently insufficient. The frequency of validated VHL mutations was 25%, which is somewhat below the mutation rates reported in clear cell renal cell carcinoma (reviewed in Gossage et al 13 ). The two missense mutations, c.194C4T and c.461C4T, have been described in both sporadic and hereditary clear cell renal cell carcinomas.…”
Section: Discussionmentioning
confidence: 72%
“…We used a whole genome amplification step, because the yield of DNA extracted from the tumor cells in the cyst walls was frequently insufficient. The frequency of validated VHL mutations was 25%, which is somewhat below the mutation rates reported in clear cell renal cell carcinoma (reviewed in Gossage et al 13 ). The two missense mutations, c.194C4T and c.461C4T, have been described in both sporadic and hereditary clear cell renal cell carcinomas.…”
Section: Discussionmentioning
confidence: 72%
“…[13][14][15] Somatic alterations in the VHL gene alterations in kidney cancer have a potential for use as prognostic and predictive markers. 16 Other somatic mutations in kidney cancers have been documented in genes involved in histone modification, including SET domain containing 2 (SETD2), Jumonji/ARID domaincontaining protein 1C (JARID1C), as well as mutations in the histone H3 lysine 27 demethylase, and SWI/SNF chromatin remodeling complex gene, PBRM1. 17,18 In this study on ccRCC tumors, we observed that though present in tumors from only a proportion of patients, the multivariate analysis indicated that the TERT promoter mutations, in agreement with previous observations in different cancer types, can define poor cause-specific patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…The pathology of ccRCC is tightly associated with aberrant elevation of HIF signaling resulted from VHL deficiency (32). PML, however, negatively regulates HIF expression through mTOR repression (3,19).…”
Section: Scp-pml Axis Downregulates Hif Signaling In Ccrccmentioning
confidence: 99%
“…ccRCC can occur sporadically (>96%) or hereditarily (<4%). Almost all hereditary ccRCC and most sporadic ccRCC are characterized by loss/ inactivation of the von Hippel-Lindau (VHL) tumor-suppressor gene (32). VHL is a substrate-binding subunit of Cullin 2 ubiquitin ligase that targets HIF1/2a for degradation.…”
Section: Introductionmentioning
confidence: 99%